2002
DOI: 10.1097/00004347-200201000-00008
|View full text |Cite
|
Sign up to set email alerts
|

CD10 is a Marker for Normal and Neoplastic Endometrial Stromal Cells

Abstract: Using the immunohistochemical technique, we investigated the expression of CD10 in normal female genital tissues, chorionic villi and decidua of early gestation, endometriotic lesions, and uterine mesenchymal tumors. The cytoplasm of normal endometrial stromal cells was consistently positive for CD10. During early gestation, decidualized endometrial stromal cells were negative or only focally positive for CD10, whereas nondecidualized stromal cells were diffusely positive. Syncytiotrophoblast was positive for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
98
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 19 publications
6
98
0
5
Order By: Relevance
“…9,15,16 Although CD10 is a useful immunohistochemical marker for the differential diagnosis of endometrial stromal sarcomas from uterine cellular leiomyomata, CD10 may also be detected in uterine cellular leiomyomata. 9,11 In this study, we demonstrated that b-catenin nuclear expression is frequently found in endometrial stromal tumors, but not in normal endometrial stroma and uterine cellular leiomyomata. Nuclear reactivity for b-catenin was noted in both of the 2 endometrial stromal nodules evaluated in this study, in 11 (92%) of the 12 low-grade endometrial stromal sarcomas evaluated and in 6 (75%) of the 8 undifferentiated endometrial sarcomas evaluated.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…9,15,16 Although CD10 is a useful immunohistochemical marker for the differential diagnosis of endometrial stromal sarcomas from uterine cellular leiomyomata, CD10 may also be detected in uterine cellular leiomyomata. 9,11 In this study, we demonstrated that b-catenin nuclear expression is frequently found in endometrial stromal tumors, but not in normal endometrial stroma and uterine cellular leiomyomata. Nuclear reactivity for b-catenin was noted in both of the 2 endometrial stromal nodules evaluated in this study, in 11 (92%) of the 12 low-grade endometrial stromal sarcomas evaluated and in 6 (75%) of the 8 undifferentiated endometrial sarcomas evaluated.…”
Section: Discussionmentioning
confidence: 62%
“…Immunohistochemical studies of endometrial stromal sarcomas have shown that they are usually positive for CD10 and both estrogen and progesterone receptors, and that they may also be positive for smooth muscle markers (such as actin and desmin). [10][11][12]14 Although diffuse strong immunoreactivity for CD10 favors the diagnosis of endometrial stromal sarcomas, 9 it is important to note that this diagnosis is not always straightforward. For example, the staining may be focal or weak, which could result in a false negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Furthermore, CD10 was identified as a sensitive and diagnostically useful marker of normal endometrial stroma and of endometrial stromal neoplasms. [20][21][22][23] In this study, antibodies against CD10 stained a majority of endometrial stromal sarcomas in a diffuse pattern, but in some cases the staining pattern was focal or patchy cytoplasmic and membranous. A similar patchy cytoplasmic and membranous pattern of staining was also observed in many solitary fibrous tumors and hemangiopericytomas.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, endometrial stromal sarcomas commonly occur in premenopausal women in contrast to the aforementioned tumors. CD10 has been considered as a specific marker for both neoplastic and non-neoplastic endometrial stromal cells [21], and probably distinguishes endometrial stromal neoplasms from others. However, there has been a report stressing CD10 positivity both in MMMT and Mullerian adenosarcoma, and indicating that CD10 is a characteristic of Mullerian system-derived neoplastic mesenchymal cells [22].…”
Section: Discussionmentioning
confidence: 99%